The evolution of trade with meat and organs in the period 2010-2020, in Romania - Diana Maria Necula; Raluca Alexandra Rǎdoi (Agrarian Economy and Rural Development - Trends and Challenges. International Symposium. 13th Edition, 2022)
This paper aims to analyze the evolution over time of the trade with meat and organs, in Romania, important foods for a balanced diet. Statistical data indicate that, although Romania has large productions, it is deficient in terms of ensuring meat consumption, especially with pork, which occupies the first position on the list of imports of agri-food products. The analysis was carried out with the help of statistical indicators: the evolution of imports and exports for the period 2010-2020 and the trade balance. The conclusions resulting from this work underline the importance of the livestock sector development, constituting an essential element for ensuring food security.
Keywords: Q17; Q02; Q13; 330; import; export; meat; trade balance; Romania